Approximation Of Continuous Set Valued Mapping And Membership Function Rough Topology - Abdunabi , Faraj. A.; Shletiet, Ahmed (Journal of Pure & Applied Sciences, 2021)
In this paper, we introduce the new definition of rough membership function using continues function and we discuss several concepts and properties of rough continuous set value functions as new results on rough the continues function and membership continues function . Moreover, we extend the definition of rough membership function to topology spaces by substituted an equivalence class by continuous functions and prove some theorems on certain types of set value functions and some more general and fundamental properties of the generalized rough sets. Our result generalized the concept of the set valued function by using rough set theory.